Student’s Perception Of Using Duolingo As An English Learning Application - Hadina, Nurul; Sari, Mezia Kemala; Yoni, Efri (Yayasan Lembaga Studi Makwa, 2023)
This study proposes to find out the student perception toward the use of Duolingo as an English learning application, Duolingo as a motivation tool to increase their motivation for learning English, and aspects of language that can be improved by language skill practice items on Duolingo. This study was quantitative research by using questioner as the data collection technique. This study was conducted on August 16, 2021, with the ninth-grade students at SMP Muhammadiyah Padang Panjang. The sample of this study consists of 16 students. The result showed that a lot of students gave a positive response to their experience using Duolingo based on the questionnaire. Duolingo is useful and helpful and it brings motivational benefits for students in English learning. Moreover, it shows that they easily master the fourth language skills and even practice their English in their daily life. Duolingo provides many uses for students as an English learning application. The use of Duolingo can help students learn English interestingly and make the learning process more enjoyable. Therefore, the use of Duolingo is recommended for English learning to help students improve their language learning abilities. Abstrak Penelitian ini bertujuan untuk mengetahui persepsi siswa terhadap penggunaan Duolingo sebagai aplikasi pembelajaran bahasa Inggris, Duolingo sebagai alat motivasi untuk meningkatkan motivasi belajar bahasa Inggris dan aspek bahasa yang dapat ditingkatkan dengan item latihan keterampilan bahasa di Duolingo. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan kuesioner sebagai teknik pengumpulan data. Penelitian ini dilaksanakan pada tanggal 16 Agustus 2021 pada siswa kelas IX SMP Muhammadiyah Padang Panjang. Sampel penelitian ini berjumlah 16 siswa. Hasil penelitian menunjukkan bahwa banyak siswa yang memberikan respon positif terhadap pengalaman mereka menggunakan Duolingo berdasarkan kuisioner yang disebar. Duolingo bermanfaat, membantu dan dapat memotivasi siswa dalam belajar bahasa Inggris. Selain itu, hasil penelitian menunjukkan bahwa mereka dengan mudah menguasai keempat keterampilan bahasa dan bahkan mempraktekkan bahasa Inggris mereka dalam kehidupan sehari-hari. Duolingo memberikan banyak kegunaan bagi siswa sebagai aplikasi pembelajaran bahasa Inggris. Penggunaan Duolingo dapat membantu siswa untuk belajar bahasa Inggris dengan cara yang menarik dan membuat proses belajar menjadi lebih menyenangkan.Oleh karena itu, penggunaan Duolingo direkomendasikan untuk pembelajaran bahasa Inggris untuk membantu siswa meningkatkan kemampuan belajar bahasa mereka.